PERAN STRATEGI PEMBELAJARAN AKTIF DALAM PENINGKATAN DAYA SERAP DAN PEMBENTUKAN SIKAP TAWADHU SISWA KELAS XI SEKOLAH MENENGAH KEJURUAN AL-ISLAM SURAKARTA - Arfian Darma Jati; Mukhlis Faathurrohman (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the role of active learning strategies in improving students’ learning absorption and fostering the attitude of tawadhu in Qur’anic learning among eleventh-grade students at SMK Al-Islam Surakarta in the 2025/2026 academic year. The study employed a descriptive qualitative approach. Data were collected through classroom observation, in-depth interviews, and documentation. The research participants included Qur’an subject teachers, eleventh-grade students, and supporting instructional documents. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings reveal that active learning strategies were implemented through group discussions, interactive question-and-answer sessions, presentations, and reflection on the values contained in Qur’anic verses. The implementation of these strategies created a more participatory, communicative, and contextual learning environment. In the cognitive domain, active learning was proven to enhance students’ learning absorption, as reflected in their ability to understand the meaning of the verses, restate the material in their own words, and achieve better learning outcomes. In the affective domain, these strategies also contributed to the development of tawadhu, including respect for peers’ opinions, polite behavior, openness to correction, and respectful attitudes toward teachers.